Quantification of the cross-sectoral impacts of waterweeds and their control in Ghana - Akpabey, Felix Jerry (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2012)
The Akosombo Dam on the Volta River in Ghana was built in 1963 to provide cheap energy to fuel industry and to accelerate the economic growth of the country. It provides hydroelectric power, enhanced fishing and water transportation upstream, and improved opportunities for irrigated farming, especially in the lower reaches, and their attendant economic multiplier effects. A few years after the construction of this major dam, a rapid expansion of industrialization took place in Ghana. This brought about an exponential increase in demand for more electrical power. This led to the construction of a smaller dam at Akuse, downstream of the Akosomho Dam in 1981 and the formation of a headpond at Kpong. The impoundment of the river at the two sites (Akosombo and Kpong) caused an alteration in the existing ecological and biophysical processes in the river basin, including a slowing of the flow of the river, upstream and downstream. Changes in the natural processes, such as a reduction in the flow of the river and an increase in nutrient status of the water, resulted in an invasion of aquatic weeds, increasing the density of aquatic snails (intermediate hosts of schistosomiasis), silting and closure of the estuary, as well as other more subtle effects. The invasion of the river's main course and the dams by aquatic plants led to a corresponding reduction of navigable water both upstream and downstream. The aim of this thesis was to quantify the impact and control of waterweeds, especially water hyacinth, Eichhornia crassipes (Mart) Solms-Laubach (Pontederiaceae), in Ghana. A floral survey on the Kpong Headpond recorded 49 emergent, 12 free floating and I submerged aquatic plant species, many of which were indigenous, but the exotic or introduced water hyacinth was recorded at most of the sampling sites, and was the most abundant and had the biggest impact on the utilization of the water resource. Mats of water hyacinth served as substrates for other, indigenous species to grow out into the main channel of the headpond, including the intake point of the Kpong head works of the Ghana Water Company Limited (GWCL) and landing sites for boats. These mats resulted in a reduction of the fish (fin and shell) harvest, reducing the annual production to far below demand. Water hyacinth was also shown to have severe health implications. A survey of the Ministry of Health records showed that the prevalence of both urinary and intestinal schistosomiasis had risen significantly over time as the abundance of waterweeds, most notably water hyacinth, increased, and ranged between 70% and 75% but up to 100% in some lakeside communities. Based on the work done by an NGO on board the medical boat ("Onipa Nua "), losses in terms of money due to the effect on health of the aquatic weed infestations on the Volta River in 2006 amounted to US$ 620,000. Economic losses due to invasive alien aquatic weeds were also calculated on the Oti River Arm of Lake Volta. It was estimated that about US$2.3 million per annum would be lost to the Volta Lake Transport Company and individual boat transport operators if this section of the river were 100% covered by aquatic weeds (water hyacinth and Salvinia molesta D.S. Mitchell (Salviniaceae)). It was also estimated that US$327,038 was spent annually in monitoring and managing the weeds in the Oti River. Control interventions for aquatic weeds have been implemented in river systems in Ghana. The biological control agents Neochetina bruchi Hustache (Coleoptera, Curculionidae) and Neochetina eichhorniae Warner (Coleoptera, Curculionidae) have been used on water hyacinth infestations in the Oti River Arm of Lake Volta, the Tano River and the Lagoon complex in the south-western part of the country. Cyrtobagous salviniae Calder and Sands (Coleoptera: Curculionidae) has been used to control salvinia, and Neohydronomous affinis Hustache (Coleoptera: Curculionidae) to control water lettuce, Pistia stratiotes Lilmaeus (Araceae) in the Tano River and Lagoon complex. Although these projects have been regarded as successful, they have relied on research from elsewhere in the world and no postrelease quantification has been conducted. In evaluating the impact of the biological control agents Neochetina bruchi and Neochetina eichhorniae weevils on water hyacinth infestations in the Tano River, fresh adult feeding scars were recorded as well as the numbers of adult weevils on each water hyacinth plant sampled at six sites. Despite being released in 1994, weevil numbers and resultant damage to plants in the Tano Lagoon was low in comparison to other regions of the world where these agents have been used. The main reason for this is that this lagoon floods seasonally, washing weevil-infested plants out to sea. Water hyacinth then re-infests the lagoon from seed and the weevil populations are low. To resolve this situation, two courses of action are proposed. The first is to mass rear the weevils along the shore of the lagoon and release them when the first seedlings recruit. The second proposal is that additional agents that have shorter lifecycies and are more mobile than the weevils should be released. To this end, the water hyacinth mirid, Eccritotarsus catarinensis (Carvalho) (Hemiptera: Miridae) was imported from South Africa and released onto the Tano Lagoon in 2009. Retrospective laboratory host specificity trials were conducted on Neachetina eichharniae and Neachetina bruchi weevils 15 years after their release into Ghana to see if any variation in their host ranges had occurred. Considerable damage was inflicted on the E. crassipes leaves by the Neachetina weevils, while little feeding damage was recorded on both Heteranthera callifalia Kunth. (Pontederiaceae) and Eichharnia natans (P.Beauv.) Solms (Pontederiaceae). All the weevils introduced on H callifalia and E. natans died after the first week. This study served to confirm the host specificity and thereby the safety of these agents. Invasive alien aquatic macrophytes have negative impacts on the environment and economy of Ghana. The control of these weeds is essential to socioeconomic development and improved human health standards in riparian communities. Biological control offers a safe and sustainable control option, but requires diligent implementation. However, aquatic weed invasion is more typically a result of the anthropogenically induced eutrophication of water bodies, and this is the main issue that has to be addressed.
Keywords: Water hyacinth -- Control -- Environmental aspects -- Ghana; Alien plants -- Research -- Ghana; Introduced organisms; Economic development -- Social aspects -- Research -- Ghana